Efficacy of Intra-Articular Injection of Platelet Rich Plasma and Hyaluronic Acid in Early Knee Osteoarthritis – Case Series. Issue 1 (23rd May 2018) - Kurapati, Krishnaiah; Tapadia, Sanjay; Rao, Madhusudhan; Anbarasu, Kavitha; Verma, Vinod Kumar; Beevi, Syed Sultan
Higher prevalence and growing burden of knee Osteoarthritis (OA) combined with recent safety concerns about pharmacological interventions has increased demand for new effective technologies for its management. Need of the hour is an innovative treatment alternative which may repair cartilage damage rather than just reduce symptoms of pain. Hyaluronic acid (HA) and PRP has been shown to relieve pain and symptoms as well as slow the progression of disease as stand-alone therapy. Treatment combining these modalities could be particularly hopeful owing to their positive and diverse interaction among themselves. Combinational treatment using both PRP and HA was performed on a series of 12 patients with early stage primary knee OA who fulfilled all the designated inclusion and exclusion criteria. All the patients were evaluated before and after treatment (1, 3, 6 and 12 months) by physical examination, assessment of VAS for pain, WOMAC, IKDC, KOOS and OKS to record the patient-reported improvement in pain, functionality and quality of life (QOL). 2-tailed Mann Whitney U Test was performed to assess the effect of treatment at different follow-up times of all the clinical scores. Whereas, Pearson correlation coefficient was done to evaluate the correlation between different clinical scores. For all tests, p < 0.05 was considered significant. All patients showed statistically significant improvement in all orthopedics scores evaluated. VAS score was improved significantly from 3.00 ± 0.49 at baseline to 1.57 ± 0.41 ( p = 0.031) in Grade I and 3.60 ± 0.51 at baseline to 2.10 ± 0.29 ( p = 0.031) in Grade II patients at 6 months' follow-up respectively. Other scores followed similar trends with statistically significant improvement at 6 months' follow-up which maintained throughout till end of the study period. All patients treated experienced strong functional improvement and substantial gains in pain relief, functionality and QOL. Hence our preliminary findings suggest that combined PRP and HA procedure is safe and potentially efficacious, which merits further investigation in large clinical settings and also in controlled clinical trials with long-term follow-ups. Focal Points: Bench side: Platelet Rich Plasma (PRP) deliver a large pool of signalling proteins including growth factors and cytokines to the local milieu driving the tissue regeneration and repair mechanisms which when combined with high molecular weight cross-linked hyaluronan could bestow greater viscoelastic properties and alleviate the symptoms of osteoarthritis. Bedside: Osteoarthritis (OA) is a chronic degenerative disease and there is no cure for OA except medical management and partial/total knee replacement in advanced stage. PRP along with HA could have the therapeutic potential to promote cartilage regeneration and inhibit inflammation synergistically by decreasing the friction coefficient and minimizing wear. Community: The burden of OA on quality of life, disability and health care utilization is quite high. Combined PRP and HA could be an effective single-dose treatment modality restoring the functional activities and considerably reducing effective cost of the treatment. Governments and regulatory agencies: The technology to obtain PRP is FDA-approved and its safety and efficacy has been well established through several clinical studies. Regulatory agencies should consider the evidences put forth by the researchers and sanction grants to investigate in larger clinical settings and also in controlled trials with different ethnicities with long-term follow-ups.